Everyone's gone to the moon - Norman, Philip (London : Arrow, 1995)
A satire on British journalism through the eyes of a young reporter from the provinces who lands a job on Fleet Street. Added action is provided when he falls in love with a manipulative woman reporter who is the editor's
Keywords: Journalists; Humorous fiction; Journalism